Localization of pulmonary stretch receptors in the airways of the dog - Miserocchi, G. (1973)
1. During respiratory efforts against a closed airway, the afferent activity of vagal fibres from pulmonary stretch receptors does not appreciably increase during the inspiratory phase because the lung is prevented from expanding. 2. Occlusion at different levels of the airways allows the localization of pulmonary stretch receptors in the tracheo-bronchial tree. 3. 144 fibres from pulmonary stretch receptors on the left side of the tracheo-bronchial tree have been studied in eleven dogs and their localization was as follows: 17·4% in the upper half of the intrathoracic trachea, 27·1% in the lower half of the intrathoracic trachea and the carina, 11·1% in the main bronchus, 13·9% in the upper lobe and 30·5% in the lower lobe. 4. From the surface area of the tracheo-bronchial tree at different levels on the assumption of a total of 2000 stretch receptors on each side, their average concentration was as follows: 34·8% receptors/cm(2) in the upper half of the intrathoracic trachea, 54·2/cm(2) in the lower half of the intrathoracic trachea, 56·8/cm(2) in the main bronchus, 0·37/cm(2) in the intrapulmonary airways. 5. Occlusion of the main bronchus caused an increase of the eupnoeic oesophageal pressure swing by about 75% whereas occlusion of the inferior lobar bronchus led to an increase of only 20%. Therefore the reflex effects induced on the respiratory activity by occluding the airways at various levels show the greatest importance of the hilar portions of the airways where the concentration of pulmonary stretch receptors has been found to be greater.